Isothiazolo[4, 3-b]pyridines as inhibitors of cyclin G associated kinase: synthesis, structure–activity relationship studies and antiviral activity1. Issue 9 (2nd September 2015) - Li, Jiahong; Kovackova, Sona; Pu, Szuyuan; Rozenski, Jef; De Jonghe, Steven; Einav, Shirit; Herdewijn, Piet
<x xml:space="preserve">Abstract</x> Starting from a known isothiazolo[4, 3-b]pyridine scaffold, different series of novel, potent GAK ligands were synthesized.